Pengaruh Model AIDA Melalui Instagram Terhadap Keputusan Pembelian Konsumen Panda Ramen - Cahyadi, Ivanka Apriella; Sirait, Tongam (Jurnal sosial dan sains, 2025)
This study aims to examine the influence of Attention, Interest, Desire, and Action (AIDA) in digital marketing through Instagram on consumers' purchase decisions at Panda Ramen. The research employed a quantitative approach by distributing questionnaires to 96 respondents using purposive sampling. The collected data were analyzed using SPSS through Exploratory Factor Analysis to obtain factor scores, which were then examined using multiple linear regression analysis. The results of the analysis show that partially the Attention, Desire, and Action variables have a significant effect on purchasing decisions, while the Interest variable does not have a significant effect on purchasing decisions of Panda Ramen consumers. Simultaneously, the four variables also show a significant effect on purchasing decisions of Panda Ramen consumers. Of the four variables, Action is the factor that has the most dominant effect on purchasing decisions. The regression coefficient values ​​of each variable are: Attention (0.204), Desire (0.208), Action (0.551), and Interest (0.055) which are not significant because the p-value is above 0.05. These findings are expected to provide a foundation for Panda Ramen’s management to optimize their digital marketing strategies, particularly by creating Instagram content that can effectively attract attention, evoke desire, and encourage consumers to take purchasing action.